Potencial de geração de energia elétrica a partir da digestão anaeróbia de esgoto sanitário - Medeiros, Sabrina de (2015)
New energy alternatives, through renewable energy sources, are the object of study throughout the world due to its important contribution to the diversification of the energy matrix of the countries, reducing their dependence on petroleum derivatives and other non-renewable energy sources and also, consequently, reducing the environmental impact from its burning. Power generation from methane derived from the anaerobic digestion of sewage, incorporates the sustainable use of renewable natural resources with the rational and efficient use of energy, by using what is usually discarded, for the production of a raw material, the energy. In this regard, this study aims to address the technical aspects relating to the recovery and energetic use of the biogas created by the anaerobic treatment of sewage, evaluating the potential of power generation from that biogas in the sewage treatment plant from the city of Francisco Beltrao, in southwestern Parana, Brazil. This review is carried out from the characterization of sewage treatment plant, the estimation of methane generation capacity of the digester, and the estimated power generation of the generated methane. Knowing the power generation potential of the sewage treatment plant, data are also collected regarding the costs of implementing the system and the generated energy savings. The results confirm the economic viability of the system, with a payback period of approximately 10 months, demonstrating the importance of reusing this fuel with high potential for power generation, which is currently simply burned.